AKADEMI ILMU TATA BAHASA ARAB DI ANDALUSIA: KRONOLOGI DAN KONTRIBUSI - Arifuddin Arifuddin (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2013)
Academy of Arabic Grammatical Science of Andalusia was established from perseverance of umaro and ulama of Umawiyyah Kingdom era of West in attempts ofdeveloping Arabic in foreign land far away from its native land, Arabic Peninsula.Princes of Umawiyya Empire were aware about their falling behind compared to theirbrothers of Islamic kingdom of East. Therefore, they worked hard to succeedrevitalization movement of Arabic sciences in Andalusia. One of most importantcontributions is methodology improvement in exploring grammatical logicargumentations. The methodology was then, improved by Ibn Madha who is known withhis reconstruction of grammatical substances. Further, the contribution inspired manynext grammatical scholars. Other figure with great contribution is Ibn Malik, and he waseven said as greatest figure. His monumental works become center of grammaticalexamination of next ulamas. Key words: Andalusia, Arabic, Ibn Madha, Ibn MalikAcademy of ArabicGrammatical Science of Andalusia was established from perseverance of umaro andulama of Umawiyyah Kingdom era of West in attempts of developing Arabic in foreignland far away from its native land, Arabic Peninsula. Princes of Umawiyya Empire wereaware about their falling behind compared to their brothers of Islamic kingdom of East.Therefore, they worked hard to succeed revitalization movement of Arabic sciences inAndalusia. One of most important contributions is methodology improvement in exploringgrammatical logic argumentations. The methodology was then, improved by Ibn Madhawho is known with his reconstruction of grammatical substances. Further, thecontribution inspired many next grammatical scholars. Other figure with greatcontribution is Ibn Malik, and he was even said as greatest figure. His monumental worksbecome center of grammatical examination of next ulamas.